The Role of PAI Teacher in Educating Environmental Character Students at Junior High School Alam Lampung - Novandi, Dicky Arya; Putri, Yulita; Nurhuda, Abid (Athena: Journal of Social, Culture and Society, 2024)
Education has goals that must be achieved by students, one of which plays an important role to achieve these goals is the teacher. And in this era of disruption full of global concerns, as it is today, PAI teachers play the most important role, especially in instilling the character values of caring for the environment in their students. Not only teachers, but several schools have also promoted their program as Adiwiyata schools and have even received awards, including SMP Alam Lampung. And the purpose of this study is to describe the role of PAI teachers in educating the character of caring for the environment in students at SMP Alam Lampung. The method used is qualitative with a field study approach, collecting data using observation techniques, documentation, and interviews. After the data has been collected, an analysis is carried out by checking the validity of the data by triangulating the sources and methods, and finally concluding. The results of the study show that the role of PAI teachers includes teaching, educators, trainers, mentors, and also role models for students to instill a caring character in the environment. This can work well because it is supported by the school's vision, activities, policies, appeals, and an adequate budget